Effects of Iron, Phosphorus and Microbial Inoculum On Yield and Quality of the Grain of Wheat (Triticum Aestivum L.) - Fiuzi, Amir Hasan; Hassanzadeh , Mojtaba; Madani , Ahad (Bangladesh Journal of Botany, 2023)
Effects of iron, phosphorus and microbial inoculums on yield and quality of the grain of wheat (Triticum aestivum L.) were studied during cropping seasons of 2019 and 2020 in Khorasan Razavi province, Mashhad following a split plot experiment based on Randomized Complete Block Design with three replications. Results showed that the application of phosphorus in the presence of iron increased the grain yield. The highest grain yield (516 g/m2) was obtained from both iron foliar and bacterial application and the lowest grain yield (435 g/m2) was obtained from no iron and phosphorus treatment. Foliar iron application and supply of microbial inoculum (bacteria and fungi) at rhizosphere resulted in the highest quantity and quality of grain yield. Bangladesh J. Bot. 52(1): 171-178, 2023 (March)